FROM THE INQUISITION TO DESCARTES. THE ORIGINS OF THE MODERN SUBJECT - Godzich, Wlad (Surfaces, 1992)
An account of the discursive problematic that accompanies the emergence of the modern subject, and of the difficulties attendant upon that subject's encounter with cultural difference.